Studies on the static and dynamic properties of different types of polyester industrial yarns - Samui, Barun Kumar; Dasgupta, Saikat; Mukhopadhyay, R.; Ramesh, C.; Chakrabarty, Debabrata (Journal of the Textile Institute, 2016)
Four major types of polyester industrial yarns, viz. high tenacity (HT), high modulus low shrinkage (HMLS), low shrinkage (LS) and super low shrinkage (SLS) polyester yarns, were studied for their static and dynamic properties. An attempt has been made to establish a linkage between static and dynamic properties of these yarns with its structure and with its end applications. HMLS and HT polyester yarns have lower tan delta and work loss, which are the desired characteristics required for its end applications which include tire and conveyer belt. Higher overall orientation and higher fraction of tie molecules helped to achieve these properties in HT and HMLS polyester yarns. LS and SLS polyester yarns are mostly used for static applications. Low thermal shrinkage is the key requirement for the downstream processes of these yarns. Lower amorphous orientation in these two yarns is primarily responsible for achieving very low thermal shrinkage. A good co-relation has been established between the peak temperature of work loss (in slow speed hysteresis test) and the peak temperature of tan delta (in high-speed dynamic test).
Keywords: creep; modulus; polyester; shrinkage; tan delta; work loss